The Impact of Strategic Skills on the Effectiveness of Attaining Balanced Performance: An Exploratory Study of the Opinions of a Sample of Administrative and Scientific Leaders at Duhok Polytechnic University - Nori, Nzar R.; Mohammad, Dilshad Y. (Humanities Journal of University of Zakho, 2018)
The research seeks to demonstrate the impact of strategic skills in balanced performance at Duhok Polytechnic University by adopting a fundamental problem of (what is the effect of the skills of the strategic leaders in the effectiveness of the application of balanced performance). The researchers based on the basic hypothesis that the skills of the strategic leaders play a positive role in the effectiveness of the implementation of the balanced performance at Duhok Polytechnic University. The researchers also relied on the method of analytical description of the views of a sample of the administrative leaders at Duhok Polytechnic University amounted to (30) individuals, By designing a questionnaire that includes a set of questions divided into two parts, the first section describes the independent variable (strategic leadership skills) and the second section includes the questions that describe (balanced performance) which is an adopted variable. The researchers then used some descriptive statistical measures to diagnose the variables of the research and these statistical methods are (percentage, mean and standard deviation), added to the use of correlation coefficient in the relationship between the two variables and the use of linear regression in the statement of the validity of the hypothesis of the research. The two researchers reached the results of the statistical analysis to the main result: The skills of strategic leaders have a positive impact on the effectiveness of balanced performance at Duhok Polytechnic University. In light of this, the researchers presented some recommendations, the most important of which is the focus on the availability of the strategic leader skills to reflect the process of evaluating the performance of the organization by the most recent method evaluated is a balanced performance card.